Processing of English Idioms with Body Part Components by Native Speakers of Turkish with Intermediate Level of English (Eurasian Journal of Philology Science and Education, 2015)
The aim of the present research is to find out ways native speakers of Turkish learning English use while processing English idioms with body part components in their structure. The experiment was conducted among first year students study in different departments of Middle East Technical University (Ankara, Turkey). The results of the experiment showed that Turkish students mostly provide definitions of English idioms based on word associations, the second preference is universals, and the third option is reliance on concepts.
Keywords: idioms; English; Turkish; body parts; processing